(untitled) (Conference on English Language Teaching, 2023)
The aim of this study was to categorize the variety of meanings in semantics found on social media, particularly on Instagram accounts. The phrases, clauses, and sentences found in the comments on the Instagram account Infosumbar serve as the study’s source of data. According to Leech’s theory, this research focuses on seven different semantic meaning types. This study uses a descriptive qualitative methodology. The observation approach is the one employed to collect data for this investigation. According to the research, five different forms of semantic meaning— conceptual meaning, connotative meaning, social meaning, reflective meaning, and collocative meaning—were present in the comments on the Infosumbar Instagram account. Social meaning is the most common type of meaning (43.70%). Within specific contexts of society, social meaning helps in language interpretation and understanding. We may better understand the intended messages and prevent misunderstandings by taking into consideration the social meanings of words and expressions.